Community Participation in Managing Plurality through Cultural Literacy and Local Wisdom to Strengthen Harmony in Religious Life - Yusuf, Ramli; Matdoan, Muhammad; Zaini, Muhammad (Electronic Journal of Education, Social Economics and Technology, 2025)
The expectations of the community in Bibinoi Village, South Halmahera Regency, North Malutu Province to maintain a plural, harmonious, safe, and peaceful atmosphere of life can be created harmoniously through tolerance relations between religious communities. Moreover, Bibinoi village has currently been designated by the Forum for Religious Harmony (FKUB) of North Maluku Province as one of the pilot villages in the formation of Rasai Village. In 1974, Bibinoi village experienced a territorial boundary conflict with Piga Raja village, and a conflict with sara nuances in 1999/2000. This study uses a qualitative approach to explore or photograph the social conditions of the community objectively, with observation, interview and documentation methods The results of the study indicate that efforts to manage ethnic plurality have been carried out through citizen participation in two ways, namely; 1) the process of internalizing the values of character education through mutual respect, respect for differences, affection, and love for fellow human beings becomes the main glue in the family environment, and 2) the transformation of cultural values of local wisdom in the form of certain customs or traditions that are considered good as a source of moral teachings must be reconstructed as an awareness of a collective movement for the development of the socio-religious life of the people of Bibinoi village.